Dogs as Pets and Pests: Global Patterns of Canine Abundance, Activity, and Health. (3rd May 2021) - Bryce, Caleb M
Synopsis: Dogs ( Canis familiaris ) were the first domesticated species and, at an estimated population of 1 billion individuals, are globally ubiquitous today. Describing the tremendous morphometric diversity and evolutionary origins of dogs is a scientific endeavor that predates Darwin, yet our interdisciplinary understanding of the species is just beginning. Here, I present global trends in dog abundance, activity, and health. While the human–dog relationship has for millennia been close, it is also complicated. As pets, companion dogs are often treated as family members and constitute the largest sector of the ever-growing >$200 billion USD global pet care industry. As pests, free-roaming dogs are an emerging threat to native species via both predation and nonconsumptive effects (e.g., disturbance, competition for resources, and hybridization). Furthermore, I briefly discuss mounting evidence of dogs as not only infectious disease reservoirs but also as bridges for the transmission of pathogens between wild animals and humans in zoonotic spillover events, triggering intensive dog population management strategies such as culling. Dog mobility across the urban-wildland interface is an important driver for this and other adverse effects of canines on wildlife populations and is an active topic of disease ecologists and conservation biologists. Other canine scientists, including veterinary clinicians and physiologists, study more mechanistic aspects of dog mobility: the comparative kinetics, kinematics, and energetics of dog locomotor health. I outline the prevalent methodological approaches and breed-specific findings within dog activity and health research, then conclude by recognizing promising technologies that are bridging disciplinary gaps in canine science.